The Relationship Between Emotion Suppression and Obsessive-Compulsive Disorder: The Mediating Role of Mindfulness - SeyedEbrahimi, Seyed AliAsghar; Hojjati Hamedani, Ata; Loshgani, Vida (Mental Health and Lifestyle Journal, 2024)
This study aimed to investigate the relationship between emotion suppression and obsessive-compulsive disorder (OCD) symptoms, with mindfulness as a mediating variable in a non-clinical adult population. The research employed a descriptive correlational design. A total of 390 adult participants from Tehran were selected based on the Morgan and Krejcie sampling table using convenience sampling. Standardized self-report measures were used, including the Emotion Regulation Questionnaire (ERQ) for emotion suppression, the Five Facet Mindfulness Questionnaire (FFMQ) for mindfulness, and the Obsessive-Compulsive Inventory-Revised (OCI-R) for OCD symptoms. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlations, and AMOS-21 for structural equation modeling (SEM) to test the hypothesized mediation model. Descriptive results indicated moderate levels of emotion suppression (M = 18.74, SD = 4.89), average to high levels of mindfulness (M = 123.61, SD = 15.43), and elevated but non-clinical levels of OCD symptoms (M = 34.25, SD = 8.76). Emotion suppression was positively correlated with OCD symptoms (r = .52, p < .001), while mindfulness was negatively correlated with both emotion suppression (r = –.46, p < .001) and OCD symptoms (r = –.48, p < .001). The SEM analysis demonstrated good model fit (χ²/df = 2.19, RMSEA = 0.056, CFI = 0.95), and confirmed that mindfulness significantly mediated the relationship between emotion suppression and OCD symptoms. The indirect effect was statistically significant (β = 0.16, p < .001), indicating partial mediation. The findings suggest that mindfulness plays a protective and mediating role in the relationship between emotion suppression and OCD symptoms. Enhancing mindfulness may reduce the psychological impact of maladaptive emotion regulation strategies and serve as a valuable target in preventive and therapeutic interventions for OCD.